The transformation from professional training to the tertiary education in Colombia: SENA case - Franco Rincón, José Luis
The following article is an insight which came up with as a result of a research process upon the pedagogical practices at SENA and pretends to pose certain questions and discussions about the step forward of the institution over the tertiary education. This process has motivated a series of discussions, not only inside SENA but also in the universities over the nature of the vocational training and how it is nucleated into the tertiary education and the implications which it raises in terms of curriculm, teleology and administration.